Analisis Konflik Penertiban Pedagang Kaki Lima (PKL) di Jalan Permindo Kota Padang - Putri Maisanda; Putri Febri Wialdi (Lembaga Yasin AlSys, 2026)
The conflict surrounding the enforcement against street vendors (Pedagang Kaki Lima, PKL) on Jalan Permindo in Padang City began with the revocation of Padang Mayor’s Decree Number 438 of 2018 and the enactment of Padang Mayor’s Decree Number 644 of 2024 on Street Vendor Locations and Schedules, which removed the formal legality of Permindo street vendors without adequate socialization or relocation solutions. This study aimed to analyze the conflict over street vendor enforcement on Jalan Permindo resulting from changes in local government policy, focusing on the factors triggering the conflict, the dynamics of the conflict between street vendors and Satpol PP officers, and the impacts of enforcement on street vendors, regulatory officers, and the overall condition of the Permindo area. A qualitative approach with a descriptive–analytical design was employed, with data collected through interviews and documentation, and analyzed with reference to Randall Collins’s conflict theory. The findings show that the conflict over street vendor enforcement on Jalan Permindo constitutes a structural conflict triggered by policy changes enacted without effective communication and dialogue. Based on Randall Collins’s conflict theory, the conflict is shaped by ineffective symbolic interaction, power imbalances without meaningful participation of street vendors in decision-making, structural injustice in the relocation process, strong solidarity among street vendors, and divergent symbolic meanings of “order”—for the government—and “livelihood”—for the street vendors. The conflict has led to the loss of livelihoods for street vendors, disruption of public order, and a decline in economic activity in the Jalan Permindo area. These findings underscore that the design and implementation of street vendor enforcement policies must take into account structural justice, sustained communication, and meaningful participation of affected groups.